Tipologi Kompetensi Spritual Berbasis Konsep Syakilah dan Implikasinya Terhadap Gaya Mengajar Guru Pendidikan Agama Islam - Mumu Zainal Mutaqin; Ahmad Rofiq; Syaefulloh Syaefulloh; Surip Surip (Tarqiyatuna: Jurnal Pendidikan Agama Islam dan Madrasah Ibtidaiyah, 2026)
This study aims to provide both a conceptual and practical foundation for formulating the teaching style of Islamic Education teachers that is not only pedagogically competent, but also possesses spiritual depth capable of transforming Islamic values into the learning process in a concrete and sustainable manner. The research method employed is qualitative with a library research approach. Data collection techniques were carried out by collecting, reading, and analyzing various written sources such as Qur’anic exegesis books, scholarly books, academic journals, and previous research findings, which were then analyzed using analytical techniques to identify, classify, and interpret the concepts that became the focus of the study. The typology of spiritual competence based on the concept of syakilah explains that every individual acts according to the tendencies of his or her soul. This typology has implications for teachers’ teaching styles, ranging from textual to contextual approaches, and also influences the quality of pedagogical interaction and the formation of students’ character. In order to realize an integrative and transformative Islamic Education learning process, teachers are expected not only to transfer knowledge but also to instill values and shape Islamic personality.